La participation démystifiée - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Vulgarisation participative. Aperçu de trois projets de développement agricole en AfriqueSkat.LBL/SDC (1998)Vadianstrasse 429000 St.Gallen - SUISSE99 pagesISBN 3-908001-78-1Prix : 50 FF/7, 62 e